Gendering Women: Body, Power and the Processes of Subjectivation - Ahmad, Farhan (Journal of Education Culture and Society, 2023)
Thesis. This study tends to show how various social, cultural, and institutional factors work to discipline women by controlling their bodies at on one level and their thought process at another level. Concept. The everyday life of women is a space in which the operation of power is manifested through various disciplinary techniques and punitive methods. The basis of such regulations is the result of the construction of gendered bodies. Results and conclusion. The study sheds light on the ways the body is produced, shaped, and controlled by gendered social norms. The body is repeatedly gendered, and asked to conform to dominant gender norms. These factors affect women’s social and sexual behaviour and place them in a subservient position. The study reveals how while generating notions about the other ‘gender’, the basic essence of ‘being human’ is often neglected. The claims for the equal space of women are to be fulfilled by formulating the possibility of a space for them which can go beyond the justified constructions of society.